2022
DOI: 10.1002/adma.202200659
|View full text |Cite
|
Sign up to set email alerts
|

Review of Semiconductor Flash Memory Devices for Material and Process Issues

Abstract: Vertically integrated NAND (V‐NAND) flash memory is the main data storage in modern handheld electronic devices, widening its share even in the data centers where installation and operation costs are critical. While the conventional scaling rule has been applied down to the design rule of ≈15 nm (year 2013), the current method of increasing device density is stacking up layers. Currently, 176‐layer‐stacked V‐NAND flash memory is available on the market. Nonetheless, increasing the layers invokes several challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 128 publications
0
43
0
Order By: Relevance
“…Therefore, these two figures indicated that the rapidly increased V BL,reset limited the N to only 50. However, this estimation was based on the impractical device dimension, and the more practical size of the TFT was assumed for the eventual V-TFT-PcRAM (channel-hole diameter/single-layer thickness ∼130/25 nm) . In this case, the contact resistance between the IGZO and ITO interface should be considered for scaled dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these two figures indicated that the rapidly increased V BL,reset limited the N to only 50. However, this estimation was based on the impractical device dimension, and the more practical size of the TFT was assumed for the eventual V-TFT-PcRAM (channel-hole diameter/single-layer thickness ∼130/25 nm) . In this case, the contact resistance between the IGZO and ITO interface should be considered for scaled dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…Nonvolatile memory (NVM) devices with high switching speeds and high-density integration should be developed for the effective implementation of artificial intelligence (AI) technologies [ 1 ]. Because of the low cost and high compatibility of flash memory for complementary metal-oxide-semiconductor (CMOS) fabrication, silicon-based flash memories are the current market leaders for NVMs [ 2 ]. However, owing to physical limitations, we have reached the limit for increasing the memory density [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Flash memory is an example of NVM and has been widely applied in electronic devices. 2 With the advance of science and technology, memory not only needs to be small to store a huge amount of information but also requires faster write and read speeds. 3,4 On the other hand, low-energy consumption is also required for developing memory due to the wide application of portable electronic products.…”
Section: Introductionmentioning
confidence: 99%
“…For nonvolatile memory (NVM), the contents which were stored previously will be retained even after removing the power supply . Flash memory is an example of NVM and has been widely applied in electronic devices . With the advance of science and technology, memory not only needs to be small to store a huge amount of information but also requires faster write and read speeds. , On the other hand, low-energy consumption is also required for developing memory due to the wide application of portable electronic products. Because of the physical limit of the gate oxide, flash memory cannot simultaneously fulfill storage needs and size reduction .…”
Section: Introductionmentioning
confidence: 99%